The Importance of the Activity-Based Approach in Developing Effective Students for Educational Activities - Falah, Moch. Fajarul; Mukhlisah; Khairunnidaq, Desi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
The activity-based curriculum has been widely applied in Arabic language learning. This approach emphasizes active student engagement in the learning process through a variety of interactive and engaging activities. The goal is to create a dynamic, student-centered learning environment that encourages language acquisition, motivation, and overall language proficiency. This study uses a descriptive-analytical method. The most important findings of this study are: 1) Exploring the benefits of combining activities relevant to students’ interests and real-life contexts, thus increasing their engagement and motivation, 2) The importance of designing activities that accommodate different learning styles and cover a variety of language skills, such as reading, writing, listening, and speaking, 3) The role of teachers as facilitators and facilitators in the activity-based curriculum, 4) The existence of challenges and considerations in implementing the activity-based curriculum, such as the availability of resources and cultural considerations, 5) The activity-based curriculum offers a promising approach to learning Arabic, as it encourages active learning, fosters critical thinking, and provides opportunities for collaborative learning experiences. Teachers can also enhance the overall language teaching experience and provide students with the language skills necessary for personal and professional growth.